Some of the opinions Sartaeva S.S. on provision of labor safety and social protection of population (Journal of actual problems of jurisprudence, 2018)
This paper investigates the theoretical questions associated to the right to the protection of human life andhealth, assessment of national law and compliance to international standards.Keywords: safety labour, investigation of accidents, work injuries, occupational disease, representation.